Dynamic human liver proteome atlas reveals functional insights into disease pathways - Lili Niu; Philipp E Geyer; Rajat Gupta; Alberto Santos; Florian Meier; Sophia Doll; Nicolai J Wewer Albrechtsen; Sabine Klein; Cristina Ortiz; Frank E Uschner; Robert Schierwagen; Jonel Trebicka; et al. (Molecular Systems Biology)
Abstract Deeper understanding of liver pathophysiology would benefit from a comprehensive quantitative proteome resource at cell type resolution to predict outcome and design therapy. Here, we quantify more than 150,000 sequence‐unique peptides aggregated into 10,000 proteins across total liver, the major liver cell types, time course of primary cell cultures, and liver disease states. Bioinformatic analysis reveals that half of hepatocyte protein mass is comprised of enzymes and 23% of mitochondrial proteins, twice the proportion of other liver cell types. Using primary cell cultures, we capture dynamic proteome remodeling from tissue states to cell line states, providing useful information for biological or pharmaceutical research. Our extensive data serve as spectral library to characterize a human cohort of non‐alcoholic steatohepatitis and cirrhosis. Dramatic proteome changes in liver tissue include signatures of hepatic stellate cell activation resembling liver cirrhosis and providing functional insights. We built a web‐based dashboard application for the interactive exploration of our resource ( www.liverproteome.org ).